The integrated Islamic education: principles and needs for thematic approaches - Salleh, Mohamad Johdi (2009)
The revelation of the first surah of the Holy Quran delivered by Malaikat Jibril A.S. to the Prophet S.A.W. is concerning education. The significance, variety and benefit of education were mentioned directly and indirectly in many surahs. The readers of the Qur’an are frequently requested to use their senses to learn, study and understand truly the meanings. They need to generate dynamically their mind, sight, aural, oral capabilities and deed in order to acquire the gist. These were practiced and manifested during the life of the beloved Prophet S.A.W., the Companions and early generation of Muslim scholars during the glorious era of Islamic Civilization. This is to show that Islam is very meticulous in this vital aspect of the development, progress and accomplishment of human being in the present world and akhirat.